Cloned fusion product from a rare t(15;19)(q13.2;p13.1) inhibit S phase in vitro. Issue 7 (1st July 2005) - Haruki, N; Kawaguchi, K S; Eichenberger, S; Massion, P P; Gonzalez, A; Gazdar, A F; Minna, J D; Carbone, D P; Dang, T P
Abstract : Background: Somatically acquired chromosomal translocation is a common mechanism of oncogene activation in many haematopoietic tumours and sarcomas. However, very few recurrent chromosomal translocations have been reported in more common epithelial tumours such as lung carcinomas. Methods: We established a cell line HCC2429 from an aggressive, metastatic lung cancer arising in a young, non-smoking woman, demonstrating a t(15;19)(q13.2;p13.1). The breakpoints on chromosomes 15 and 19 were cloned using long distance inverse PCR and we determined by RT-PCR that the translocation results in a novel fusion transcript in which the 3′ end Brd4 on chromosome 19p is fused to the 5′ end of NUT on chromosome 15q. Results: In total, 128 lung cancer tissues were screened using fluorescent in situ hybridisation, but none of the tumours screened demonstrated t(15;19), suggesting that this translocation is not commonly found in lung cancer. Consistent with previous literature, ectopic expression of wild type Brd4 was shown to inhibit G1 to S progression. However, we also found that the Brd4-NUT fusion augments the inhibition of progression to S phase compared with wild type Brd4. Conclusion: Alteration in cell cycle kinetics is important in tumorigenesis, although the exact role of Brd4-NUT fusion protein in the pathogenesis of lung cancers remains unclear and need to be further elucidated.